The Implementation of the Amtsilati Method in Reading the Book Safinatun Najah to Improve Students’ Motivation in Learning Arabic at MTs Hidayatus Syubban, Karangroto, Genuk, Semarang - Inas Umniyyah; Aliwan; Abdul Hakim (Yayasan Azhar Amanaa Yogyakarta, 2026)
Amtsilati learning is an additional program conducted outside regular class hours to improve students’ ability to read Safinatun Najah. The Amtsilati method is a fast and practical approach to understanding basic Arabic grammatical rules (nahwu and sharaf), enabling students to read classical Islamic texts without vowel marks. Developed by Taufiqul Hakim from Pondok Pesantren Darul Falah, this method emphasizes systematic and gradual mastery of Arabic linguistic principles. This study aims to examine the implementation of the Amtsilati method in learning to read Safinatun Najah at MTs Hidayatus Syubban, describe the learning process, and identify supporting and inhibiting factors, including its impact on students’ motivation in learning Arabic. The research uses a qualitative field approach with data collection techniques such as observation, interviews, and documentation. Data analysis is conducted through data condensation, data display, and conclusion drawing, while validity is ensured through triangulation of sources and methods. The findings show that learning planning includes formulating objectives, selecting materials, and determining teaching methods. The program is intended for non-boarding students using materials from Amtsilati volumes I–V, Tatimmah, Qaidah Amtsilati, and Nadzom Amtsilati, delivered through a classical classroom model. Learning activities include opening (prayer and nadzom recitation), core activities (material explanation and reading practice), and closing (evaluation and prayer). The results indicate that the method is implemented systematically and effectively, improving students’ ability to read Safinatun Najah and increasing their motivation in learning Arabic. This is reflected in students’ confidence, active participation, and willingness to advance. However, obstacles include limited teacher creativity, differences in student abilities, and discipline issues. These are addressed through training, adjusted memorization schedules, and educational sanctions.